Pengaruh Pengungkapan Corporate Social Responsibility Pada Nilai Perusahaan dengan Ukuran Perusahaan sebagai Variabel Moderasi - Wedayanti, Luh Putri; Wirajaya, I Gde Ary (E-Jurnal Akuntansi; Vol 24 No 3 (2018), 2018)
This study aims to determine the effect of firm size in moderating the CSR disclosure relationship on firm value. This research takes object in mining company and use period for 3 year that is from year 2014-2016. The research method used in this research is associative research causality. The type of data used in this study is quantitative data. Determination of the sample in this study using nonprobability sampling method with purposive sampling technique. There are 21 mining companies that meet the criteria as sample. Data analysis technique used is Moderated Regression Analysis (MRA). Based on the result of research, show that firm size as a moderating variable can strengthen the influence of CSR disclosure on company value. That is, the larger the size of the company and the more CSR corporate disclosure then it can increase the value of the company. Keywords: CSR disclosure, firm size, firm value